2005
DOI: 10.1542/peds.2004-1833
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Septicemia in a Norwegian National Cohort of Extremely Premature Infants Receiving Very Early Full Human Milk Feeding

Abstract: ABSTRACT. Objectives. To investigate the occurrence of and risk factors for late-onset septicemia (LOS) in a national cohort of extremely premature infants who received very early full human milk feeding.Methods. A prospective study of all infants born in Norway in 1999 and 2000 with gestational age of <28 weeks or birth weight of <1000 g was performed. Extensive clinical information, including data on feeding practices and episodes of septicemia, was collected on predefined forms. LOS was defined as growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(157 citation statements)
references
References 33 publications
10
136
2
8
Order By: Relevance
“…[13][14][15][16]22 These findings suggest that similar to the effect of donor HM, mothers' own milk is associated with a decreased risk of NEC, and the association appears to be present even if HM is not the exclusive source of enteral nutrition. Our observation that HM proportion of enteral feeding in the first 2 weeks is protective against NEC is also consistent with the findings of Ronnestad et al, 23 who reported an NEC rate of 2.2% in a sample of 464 extremely low birth weight infants (birth weight <1000 g). During the study period, 98% of the infants received HM exclusively (either own mother's milk, donor HM, or both), and 96% were fed within the first 3 days of life.…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15][16]22 These findings suggest that similar to the effect of donor HM, mothers' own milk is associated with a decreased risk of NEC, and the association appears to be present even if HM is not the exclusive source of enteral nutrition. Our observation that HM proportion of enteral feeding in the first 2 weeks is protective against NEC is also consistent with the findings of Ronnestad et al, 23 who reported an NEC rate of 2.2% in a sample of 464 extremely low birth weight infants (birth weight <1000 g). During the study period, 98% of the infants received HM exclusively (either own mother's milk, donor HM, or both), and 96% were fed within the first 3 days of life.…”
Section: Discussionsupporting
confidence: 93%
“…Human milk contains numerous immunological components that directly protect infants. Studies have shown that exclusive breast-feeding reduces the risk of infectious diseases in the respiratory, gastrointestinal and urinary tracts (4)(5)(6)(7)(8) , and that it protects premature children from neonatal sepsis and necrotizing enterocolitis (9)(10)(11) . In addition, the immunological components of human milk support the development and maturation of the infant's own immune system, which may explain some of the longterm health benefits observed in breast-fed children (12) .…”
mentioning
confidence: 99%
“…Однако многим авторам удается про-демонстрировать высокую эффективность применения донорского молока по сравнению с молочными смеся-ми. Так, согласно результатам трех метаанализов, про-веденных в период с 2003 по 2007 г., основным пре- [19] показано, что корм-ление свежесцеженным материнским молоком так же, как и донорским, уменьшает риск развития позднего сепсиса у детей с экстремально низкой массой тела при рождении. Однако при последующем анализе эти дан-ные подтвердились только относительно материнского молока [20].…”
Section: при невозможности обеспечения ребенка материнским молоком неunclassified